1996
DOI: 10.1002/(sici)1097-0061(19960915)12:11<1125::aid-yea7>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a gene encoding a G protein α subunit involved in the regulation of cAMP levels in the yeastKluyveromyces lactis

Abstract: Using chromosomal DNA from Kluyveromyces lactis as template and oligodeoxynucleotides designed from conserved regions of various G protein alpha subunits we were able to amplify by the polymerase chain reaction two products of approximately 0·5 kb (P‐1) and 0·8 kb (P‐2). Sequencing showed that these two fragments share high homology with genes coding for the Gα subunits from different sources. Using the P‐1 fragment as a probe we screened a genomic library from K. lactis and we cloned a gene (KlGPA2) whose ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This further supports the finding that glucose does not stimulate cAMP synthesis through intracellular acidification. Our results also fit with results obtained in the other yeast species S.pombe (Isshiki et al ., 1992; Nocero et al ., 1994) and K.lactis (Saviñon‐Tejeda et al ., 1996) where a GPA2 homologue was found to be required for glucose‐induced stimulation of cAMP synthesis. Previously, the inability of a Ras2 val19 mutant to mediate glucose‐induced cAMP signalling was interpreted as indicating a role for the Ras proteins in transmission of the glucose signal (Mbonyi et al ., 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This further supports the finding that glucose does not stimulate cAMP synthesis through intracellular acidification. Our results also fit with results obtained in the other yeast species S.pombe (Isshiki et al ., 1992; Nocero et al ., 1994) and K.lactis (Saviñon‐Tejeda et al ., 1996) where a GPA2 homologue was found to be required for glucose‐induced stimulation of cAMP synthesis. Previously, the inability of a Ras2 val19 mutant to mediate glucose‐induced cAMP signalling was interpreted as indicating a role for the Ras proteins in transmission of the glucose signal (Mbonyi et al ., 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, it was concluded that Gpa2 is an element of the nitrogen‐sensing machinery that regulates pseudohyphal differentiation by modulating cAMP levels. On the other hand, in Schizosaccharomyces pombe (Isshiki et al ., 1992; Nocero et al ., 1994) and Kluyveromyces lactis (Saviñon‐Tejeda et al ., 1996), Gα proteins appear to be involved in the stimulation of cAMP levels in response to glucose.…”
Section: Introductionmentioning
confidence: 99%